Guira: Uma Biblioteca de Programação em Python para Prática de Simulação Robótica com CoppeliaSim - Silva, Mateus de Assis (2022)
The discipline of Sistemas Robóticos Autônomos (code DCA0440), taught at the Universidade Federal do Rio Grande do Norte’s Departamento de Engenharia de Computação e Automação has, as its main evaluation system, a set of projects to be done. Such projects address the contents taught by means of construction, testing and execution of navigation algorithms for mobile robots. Such codes are tested using the simulation platform CoppeliaSim (formerly known as VRep). An API provided by the software lets the user code to access the simulations. Even though the software is documented, implementation details usually takes time, and the lack of tutorials and (or) usage examples end up demanding an extra effort that could be dedicated exclusively to high-level algorithms themselves. Thus, this work aims to build a package (programming library) in Python (a high-level and popular language) that contains the most basic functionalities of communication with the API, according to the needs of the course. This ensures that students can focus on the navigation algorithms, as the modules will provide all the information needed, as well as a centralized documentation and usage examples, which accelerate learning